Complex Migration of Tremor Near Cholame, CA, Resolved by Seismic Array Analysis. Issue 9 (21st September 2021) - Inbal, A.; Thomas, A. M.; Newton, T.; Bürgmann, R.
Abstract: Tectonic tremor observed along the Cholame and Parkfield sections of the San Andreas Fault has previously been associated with transient slip beneath the seismogenic zone. To study tremor and associated Low Frequency Earthquakes (LFEs), we deployed three dense near‐fault seismic arrays for a period of 3 months in 2018. In early August 2018, the arrays recorded a strong 4‐day‐long deep transient that nucleated in Cholame and propagated toward the northwest. The initiation area is characterized by tremor that persists throughout the transient, while adjacent fault portions located to the northwest host more intermittent tremor. From the rate and location of tremor and LFEs, we infer a deep slip transient, whose along‐strike propagation velocity is ∼8 km/day. Secondary tremor fronts are observed to travel ahead of the main slow slip front at speeds that are 1 0 2 − 1 0 3 times faster. These rapid migrations propagate in slow slip events (SSE) slip‐parallel direction, and are sometimes observed to back‐propagate into previously ruptured segments. High‐resolution images of secondary fronts obtained by using near‐fault borehole stations indicate the active tremor band takes the shape of a narrow strain pulse that is bounded from above by the lower edge of the seismogenic zone. We estimate the stress drops associated with the secondary slip fronts are of the order of a few kPa. Frequency‐dependent analysis suggests the tremor signal is coherent at frequencies as high as 16 Hz, and that the spatial distribution of high‐ and low‐frequency tremor radiators is sometimes complementary. Plain Language Summary: Tectonic tremor is a class of seismic signals whose temporal and spectral properties are distinct from the ones associated with regular earthquakes. Tremor is generally observed along fault portions located below the seismogenic zone, and is thought to be the seismic manifestation of episodic slow slip events (SSE). Elucidating the factors controlling the tremorgenic behavior of faults is important for understanding the physics of earthquakes. To study tremor along the Parkfield‐Cholame section of the San Andreas Fault, we deployed three dense near‐fault seismic arrays in 2018. During the first days of August 2018, the arrays recorded a strong deep transient that nucleated near Cholame and propagated toward the northwest. We analyze near‐fault surface and borehole seismic data and obtain precise tremor locations. We find that tremor migrates along the fault's strike and depth at speeds that vary by about three orders of magnitude, from 5 km/day to up to 150 m/s. Rapid propagation associated with aseismic slip rates that are about 10 times faster than the tectonic rate occurs in the direction parallel to the SSE propagation, as well as backwards into previously ruptured sections. Together, these observations shed light on the complex behavior of deep fault sections. Key Points: Tremor is observed by dense seismic arrays deployed near Cholame, CA Long‐ and short‐term migration speeds inferred from precisely located tremor are observed to vary by over three orders of magnitude We provide the first evidence for Rapid Tremor Reversals (RTR) occurring on the San Andreas Fault